ANTIMICROBIAL RESISTANCE IN SEAFOODS, AND NON-THERMAL FOOD PROCESSING - Ortega Blázquez, Irene; Grande Burgos, Maria José; Martínez Viedma, Pilar; Toledo del Árbol, Julia; López Aguayo, Mari Carmen; Pérez Pulido, Rubén; Lucas, Rosario; Galvez, Antonio (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2018)
Seafoods may carry strains of bacterial pathogens resistant to clinically-used antibiotics. This review summarizes recent work on antimicrobial resistance from seafoods. Since ready-to-eat seafoods may also be at risk of transmitting antimicrobial resistance through the food chain, it is important to analyse how food processing methods may affect the bacterial populations in foods. Recent studies based on high-hydrostatic pressure applied on seafoods in combination with natural antimicrobials (bacteriocins and essential oils) indicate that the combined treatments achieve a greatest reduction of bacterial loads in the food. Nevertheless, application of high-throughput sequencing technology to study the dynamics of bacterial population surviving treatments reveals complex changes in bacterial populations during food storage. This makes necessary to further study the antimicrobial resistance in those strains surviving treatments and which may be consumed along with the processed food.